EUROCENTRIC SOCIETY, DECOLONIALISM AND THE SEARCH FOR UNIFORMIZATION OF LEGAL ORDINATIONS AND THE GLOBAL RISK THEORY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The present work discusses the idea of ​​universal protection of human rights with subsidy in the utopian solution of the Global Risk Theory of Ulrich Beck. The interest in question is a good legal relationship between the peoples of the planet and not feelings of domination, exploitation and enrichment. Thus, after a detailed analysis of the process of relativization of jurisdictionality, it is perceived that the most important is the search for legislation, one that represents the whole community, since human actions affect not only those who directly practice them, but all on the globe.